Entrapment of ciliates at the water-air interface. - Jonathan Ferracci; Hironori Ueno; Keiko Numayama-Tsuruta; Yohsuke Imai; Takami Yamaguchi; Takuji Ishikawa (PLoS ONE, 2013)
The importance of water-air interfaces (WAI) on microorganism activities has been recognized by many researchers. In this paper, we report a novel phenomenon: the entrapment of ciliates Tetrahymena at the WAI. We first characterized the behavior of cells at the interface and showed that the cells' swimming velocity was considerably reduced at the WAI. To verify the possible causes of the entrapment, we investigated the effects of positive chemotaxis for oxygen, negative geotaxis and surface properties. Even though the taxes were still effective, the entrapment phenomenon was not dependent on the physiological conditions, but was instead affected by the physical properties at the interface. This knowledge is useful for a better understanding of the physiology of microorganisms at interfaces in nature and in industry.